HUBUNGAN POSISI WRIST SAAT MENGGENGGAM SMARTPHONE TERHADAP TINGKAT NYERI PADA MAHASISWA DENGAN RISIKO CARPAL TUNNEL SYNDROME - Kurnia Putri Utami; Alfi Dian Nika Latifatul Toriq; Atika Yulianti (LPPM STIKES Siti Hajar dan Insight Power, 2023)
This research is motivated by the use of smartphones in an inappropriate position with the risk of carpal tunnel syndrome. The use of smartphones has integrated into people's social life as if they cannot be separated from their gadgets. So in this study see how a person uses his smartphone and in what position. The purpose of this study was to identify the position of the wrist when holding a smartphone, the association between the risk of carpal tunnel syndrome, and to analyze the relationship between the position of the wrist when holding a smartphone and the level of pain in students at risk of carpal tunnel syndrome. The method used is a cross sectional study, a sample of 131 people and using a two-proportion hypothesis test. Sampling by looking at the inclusion criteria and by random sampling. The data collection tool used a physical examination with a provocation test and a questionnaire, then data analysis was carried out using univariate and bivariate methods using Kolmogro-Smirnov and Spearmen.The results of the study are based on bivariate analysis where the normality test is in the position of holding a smartphone with a physical examination of CTS. In positions A and B the p-value is 0.000, then in position C the p-value is 0.001, in position D with a p-value of 0.000, and in position F the p-value is 0.006. Then the results of the 0.059 correlation show that there is a relationship between the position of the wrist when holding a smartphone and the level of pain in students at risk of carpal tunnel syndrome. In conclusion, the position with the physical examination of CTS obtained data <0.005, so H0 was rejected and H1 was accepted. Suggestions for students who have indicated symptoms of TS are expected to reduce smartphone use in a bad position so that it doesn't get worse. Keywords: Wrist Position, Physical Examination, Pain, Carpal Tunnel Syndrome, and smartphone